Property features and mental state university students of modern - Belykh S.I (Kharkov National Pedagogical University, 2013)
The results of the study of values and mental conditions of typical Ukrainian university students. It is shown that mental health - a state of psychic sphere. It is based on the general state of peace of mind, which gives adequate behavioral reaction. Moral health - a set of motivational characteristics, need and informative aspects of life. Its basis is determined by the system of values, attitudes and motivations of individual behavior. It is established that the existing level of organization of the educational process in physical education does not create the necessary framework for the effective development of physical culture of the students and getting them non-professional physical education, only partially solves the problem of their physical fitness and recreation.